OFFICIAL INVESTIGATIONS OF OFFENCES AGAINST THE ESTABLISHED PROCEDURE FOR MILITARY SERVICE - Pashchenko, Petro (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Under the conditions of martial law in Ukraine, the issue of the effectiveness of internal investigations into offences against the established procedures of military service in the Armed Forces of Ukraine has become particularly pressing. Practical experience reveals a number of shortcomings, including an excessive focus on punitive measures, insufficient consideration of the systemic factors underlying misconduct, a limited preventive role, and the risk of adverse effects on the moral and psychological well-being of service personnel. The purpose of this study is to analyze the problematic aspects of conducting internal investigations in the Armed Forces of Ukraine during martial law and to identify ways to enhance their preventive effectiveness in order to strengthen overall defence capability. M e t h o d s .The research applies systemic and structural–functional analysis, methods of synthesising law enforcement practice, and a comparative legal approach. The information base comprises the norms of current Ukrainian legislation, including laws, subordinate normative acts, and military statutes, as well as contemporary scholarly works by Ukrainian legal academics. R e s u l ts. The findings indicate that the current system of internal investigations within the Armed Forces of Ukraine is largely focused on identifying culpable individuals and imposing disciplinary measures and/or penalties, which does not ensure adequate prevention of repeated offences. The study substantiates the need to: improve the activities of specialised teams composed of trained service personnel and psychological support specialists; provide targeted training for those involved in investigations; optimise investigation timeframes to ensure the comprehensive clarification of circumstances; and intensify explanatory work among commanders and personnel regarding the grounds and procedures for internal investigations. C o n c l u s i o n s . The analysis of theoretical and practical aspects of internal investigations in the Armed Forces of Ukraine demonstrates that the existing system possesses limited preventive potential and is insufficiently oriented towards addressing the systemic causes of breaches of military discipline. The predominance of punitive measures, without due regard to psychological, organisational, and social factors, fails to guarantee a sustainable reduction in offences and may have a detrimental impact on the moral and psychological state of service personnel. The identified shortcomings highlight the need for further research, particularly the development of scientifically grounded methodologies for detecting systemic causes of misconduct, the integration of psychological and sociological approaches into investigative procedures, and the assessment of the effectiveness of adapting international practices to national conditions. Such research will contribute to the establishment of a modern, comprehensive, and effective model of internal investigations that meets legislative requirements, addresses the needs of military administration, and responds to the challenges of contemporary armed conflict.